Fluorine-free weather-resistant polyester film and preparation method thereof

By introducing silicon-titanium core-shell material and polyester raw material solid phase polycondensation to PET polyester, the weather resistance problem of polyester film in outdoor environment is solved, and efficient UV resistance and hydrolysis resistance improvement is achieved. , avoid the use of fluoride and meet environmental protection requirements.

CN119286248APending Publication Date: 2025-01-10JIANGSU YUXING FILM TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411477137.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

When used outdoors, traditional polyester films cause photooxidation and hydrolysis of ester bonds due to ultraviolet rays and humid high temperature environments, resulting in mechanical properties and color changes. Existing solutions such as fluorine-containing films are costly and environmentally contaminated, making it difficult to prepare fluorine-free and available. Polyester film with good weather resistance.

Method used

In PET polyester, a silicon-titanium core-shell material is introduced to modify titanium dioxide by silane coupling agent to form a silicon-titanium core-shell material, and a weathering masterbatch is prepared with the solid phase polycondensation with the polyester raw material. The carboxyl group after the breakage of the amino active group and the ester bond occurs. Reduce the carboxyl content and improve the hydrolysis resistance and UV resistance of polyester.

Benefits of technology

It significantly improves the UV resistance and hydrolysis resistance of polyester films, with an ultraviolet barrier rate of more than 99%, a yellowing index after UV aging is less than 3, and a retention rate of elongation at break is greater than 20%. At the same time, the use of fluoride is avoided, which satisfies the Environmental protection requirements.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a fluoride-free weather-resistant polyester film and a preparation method thereof, and relates to the technical field of polyester films, the fluoride-free weather-resistant polyester film comprises the following components by weight: 70-90 parts of a semi-dull polyethylene glycol terephthalate high-viscosity slice; 8 to 28 parts of weather-resistant master batch; the weather-resistant master batch is obtained by modifying titanium dioxide through a silane coupling agent to form a silicon-titanium core-shell material and then carrying out solid-phase polycondensation on the silicon-titanium core-shell material and a polyester raw material. According to the fluoride-free weather-resistant polyester film provided by the invention, the weather-resistant master batch is prepared by introducing a silicon-titanium core-shell material formed by modifying titanium dioxide with a silane coupling agent into PET polyester and then carrying out solid-phase polycondensation on the silicon-titanium core-shell material and the polyester raw material, so that the production cost is reduced by utilizing the synergistic effect of all the components, and meanwhile, the fluorine-free weather-resistant polyester film has the advantages that the fluorine-free weather-resistant polyester film is prepared; the prepared fluorine-free weather-resistant polyester film has excellent hydrolysis resistance and ultraviolet resistance, and the weather resistance of the fluorine-free weather-resistant polyester film is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polyester films, and in particular to a fluorine-free weather-resistant polyester film and a preparation method thereof. Background Art

[0002] Biaxially oriented polyester film (BOPET) is a film material made of polyethylene terephthalate. It has the advantages of excellent mechanical properties, electrical insulation, corrosion resistance, high transparency, and a wide operating temperature. It is widely used in packaging, insulation, consumer electronics, optical modules, films, photovoltaics and other fields.

[0003] However, traditional polyester films have some inherent defects in aging resistance. Especially when used outdoors, such as photovoltaic backsheets or building waterproofing membranes, strong ultraviolet radiation and humid and high-temperature environments will cause side reactions such as photooxidation and hydrolysis of the ester bonds in the polyester film. These reactions will cause long molecular chains to break, generate low molecular weight chain breaks, and produce carboxyl and hydroxyl groups, which will further accelerate the hydrolysis process of the ester bonds, thereby having an irreversible effect on the mechanical properties and color (yellowing) of the polyester film.

[0004] In order to solve this problem, early outdoor films usually used fluorine-containing films, and improved aging resistance by composite fluorine films or coating fluorine-containing coatings. Although this method is effective, the raw material cost of fluorine-containing films is high, recycling is difficult, and it pollutes the environment. Therefore, how to prepare a fluorine-free polyester film with excellent weather resistance is a key technical difficulty. Summary of the invention

[0005] In order to solve the problem that it is impossible to prepare a fluorine-free polyester film with good weather resistance in the prior art, the present invention discloses a fluorine-free weather-resistant polyester film. The weather-resistant masterbatch is prepared by introducing titanium dioxide modified by a silane coupling agent into PET polyester and then solid-phase polycondensing with polyester raw materials. The weather-resistant masterbatch has a large number of reactive amino active groups inside. During the aging process of polyester, the amino active groups can chemically react with the carboxyl groups formed after the ester bonds are broken to achieve a capping effect, gradually reduce the carboxyl content inside the polyester, provide continuous hydrolysis resistance, and thus significantly improve the weather resistance of the polyester film.

[0006] The technical solution adopted by the present invention to solve its technical problem is: A fluorine-free weather-resistant polyester film comprises the following components in parts by weight: 70-90 pieces of semi-matt polyethylene terephthalate high-viscosity slices; Weathering masterbatch 8-28 parts; The weather-resistant masterbatch is obtained by modifying titanium dioxide with a silane coupling agent to form a silicon-titanium core-shell material, and then solid-phase polycondensing the material with a polyester raw material.

[0007] Optionally, the components of the fluorine-free weather-resistant polyester film further include a heat stabilizer and a toughening agent; and the semi-matt polyethylene terephthalate high-viscosity slice has an intrinsic viscosity of 0.7-0.8 dL / g and a carboxyl content of 10-30 mmol / kg.

[0008] Optionally, the weather-resistant masterbatch is prepared according to the following method: (1) Add titanium dioxide, deionized water, and anhydrous ethanol to a container and stir, then gradually add PBS phosphate buffer until the pH is 10; heat up and continue stirring; then add amino silane coupling agent and continue stirring and reacting for 6-7 hours; after cooling to room temperature, centrifuge and wash until the surface liquid pH is 7, and dry the remaining solid mixture to obtain a silicon-coated silicon-titanium core-shell material; (2) Add terephthalic acid, ethylene glycol, tetrabutyl titanate, triethoxy phosphate, silicon-titanium core-shell material, and antioxidant into a container, pre-stir under the protection of inert gas, then increase the temperature and carry out solid phase polycondensation reaction under vacuum, and after cooling, granulate through a melt extruder to obtain a weather-resistant masterbatch.

[0009] Optionally, the amino silane coupling agent is selected from at least one of 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysiloxane, anilinemethyltriethoxysiloxane, N,N-dimethyl-3-aminotrimethoxysiloxane, N(2-aminoethyl)3-propylaminomethoxymethylsilane, N-β-(aminoethyl)γ-aminopropyltriethoxysilane coupling agent, N-(β-aminoethyl-γ-aminopropyl)methyldimethoxysilane, silane-PEG-amino compound, 3-aminopropyltrihydroxysilane, diethylaminomethyltriethoxysilane, γ-piperazinepropylmethyldimethoxysilane, and γ-aminopropyltrimethoxysilane.

[0010] Optionally, the titanium dioxide is at least one of rutile titanium dioxide and anatase titanium dioxide.

[0011] Optionally, the mass ratio of titanium dioxide, deionized water and anhydrous ethanol in step (1) is 100:(50-80):(20-50).

[0012] Optionally, the mass of the amino silane coupling agent in step (1) is 5-10% of the mass of titanium dioxide.

[0013] Optionally, the mass ratio of terephthalic acid, ethylene glycol, tetrabutyl titanate, triethoxy phosphate, silicon-titanium core-shell material, and antioxidant in step (2) is (80-100):(50-70):1:1:(200-260):1.

[0014] Optionally, the pre-stirring temperature in step (2) is 80-100°C and the pressure is 0.5-0.8 MPa; the pressure of the solid phase polycondensation is 220-260°C; and the temperature of the melt extrusion is 260-280°C.

[0015] Another object of the present invention is to provide a method for preparing the fluorine-free weather-resistant polyester film as described above, characterized in that it comprises the following steps: S1: sending semi-matt polyethylene terephthalate high-viscosity chips, weather-resistant masterbatch, heat stabilizer and toughening agent to the extruder for melt extrusion; S2: After passing through the die, the melt is cast behind the chilled roller to form a thick sheet, and after longitudinal stretching, transverse stretching, shaping, cooling, pulling, and winding, a fluorine-free weather-resistant polyester film is obtained.

[0016] The present invention has the following beneficial effects: The fluorine-free weather-resistant polyester film provided by the present invention is a weather-resistant masterbatch prepared by introducing titanium dioxide modified by a silane coupling agent into PET polyester to form a silicon-titanium core-shell material, and then solid-phase polycondensing the silicon-titanium core-shell material with a polyester raw material; wherein the surface amino groups of the silicon-titanium core-shell material participate in the polymerization reaction through chemical action, thereby enhancing the interface interaction and dispersibility of titanium dioxide in the polyester matrix, and significantly improving the anti-ultraviolet performance of the film, so that the prepared fluorine-free weather-resistant polyester film has an ultraviolet blocking rate of more than 99% at 280-400nm, and an ultraviolet blocking rate of more than 60kwh / m after UV aging. 2 The yellowing index is less than 3; In addition, the weather-resistant masterbatch is rich in reactive amino active groups, which can chemically react with the carboxyl groups generated by broken ester bonds during the aging process of polyester to achieve a capping effect, thereby reducing the carboxyl content inside the polyester and providing long-lasting hydrolysis resistance. The prepared fluorine-free weather-resistant polyester film has a 72h elongation retention rate of more than 20% under an environment of temperature 121°C and humidity 100%RH. DETAILED DESCRIPTION

[0017] The present invention is now further described in detail. The embodiments described below are exemplary and intended to be used to explain the present invention, but cannot be understood as limiting the present invention. All other embodiments obtained by ordinary technicians in this field without creative work based on the embodiments of the present invention belong to the scope of protection of the present invention.

[0018] When traditional polyester films are used outdoors, they are prone to photooxidation and hydrolysis reactions due to the influence of ultraviolet rays and humid and high-temperature environments, resulting in molecular chain breakage and the formation of carboxyl and hydroxyl groups. These groups will accelerate the hydrolysis process and affect the mechanical properties and color stability of the film. In order to improve aging resistance, an early solution was to use fluorine-containing films, but this method is costly, difficult to recycle, and harmful to the environment.

[0019] In addition, existing weather-resistant polyester films usually use organic anti-UV additives to improve UV aging resistance, and add polycarbodiimide, glycidyl ether / ester, isocyanate compounds, etc. to improve hydrolysis resistance. However, these additives are prone to migration failure during long-term use. For products with high requirements, adding too much additives can easily reduce other properties such as mechanical properties. At the same time, there is also the disadvantage of high cost.

[0020] In order to solve the problem that it is impossible to prepare a fluorine-free polyester film with good weather resistance in the prior art, the present invention provides a fluorine-free weather-resistant polyester film, which comprises the following components in parts by weight: 70-90 pieces of semi-matt polyethylene terephthalate high-viscosity slices; Weathering masterbatch 8-28 parts; Among them, the weather-resistant masterbatch is obtained by modifying titanium dioxide with a silane coupling agent to form a silicon-titanium core-shell material, and then solid-phase polycondensing it with a polyester raw material.

[0021] Specifically, the preferred weather-resistant masterbatch of the present invention is prepared according to the following method: (1) Add titanium dioxide, deionized water, and anhydrous ethanol to a container and stir, then gradually add PBS phosphate buffer until the pH is 10; heat up and continue stirring; then add amino silane coupling agent and continue stirring and reacting for 6-7 hours; after cooling to room temperature, centrifuge and wash until the surface liquid pH is 7, and dry the remaining solid mixture to obtain a silicon-coated silicon-titanium core-shell material; (2) Add terephthalic acid, ethylene glycol, tetrabutyl titanate, triethoxy phosphate, silicon-titanium core-shell material, and antioxidant into a container, pre-stir under the protection of inert gas, then increase the temperature and carry out solid phase polycondensation reaction under vacuum, and after cooling, granulate through a melt extruder to obtain a weather-resistant masterbatch.

[0022] The fluorine-free weather-resistant polyester film provided by the present invention does not need to add an organic anti-ultraviolet additive to improve the ultraviolet aging resistance. The weather-resistant masterbatch prepared by introducing titanium dioxide modified by a silane coupling agent to form a silicon-titanium core-shell material into PET polyester and then solid-phase polycondensing with a polyester raw material, the surface amino groups of the silicon-titanium core-shell material participate in the polymerization reaction through chemical action, the interface interaction and dispersibility of titanium dioxide in the polyester matrix are enhanced, the ultraviolet resistance of the film is significantly improved, and the yellowing index after ultraviolet irradiation is extremely low, showing excellent weather resistance; the prepared fluorine-free weather-resistant polyester film has an ultraviolet blocking rate of more than 99% at 280-400nm, and a UV resistance of 60kwh / m 2 The yellowing index is less than 3.

[0023] In addition, the weather-resistant masterbatch forms a silicon-titanium core-shell material by coating a layer of reactive silicon film on the surface of titanium dioxide. The silicon film can form a strong Si-O-Ti bond with titanium dioxide. At the same time, the weather-resistant masterbatch is rich in reactive amino active groups, which can chemically react with the carboxyl groups produced by the broken ester bonds during the aging process of polyester to achieve a capping effect, thereby reducing the carboxyl content inside the polyester and providing long-lasting hydrolysis resistance. The prepared fluorine-free weather-resistant polyester film has a 72h elongation retention rate of more than 20% under an environment of temperature 121°C and humidity 100%RH.

[0024] In order to further improve the comprehensive performance of the fluorine-free weather-resistant polyester film of the present invention, the components of the fluorine-free weather-resistant polyester film of the present invention preferably also include a heat stabilizer and a toughening agent; and the semi-matt polyethylene terephthalate high-viscosity slice has an intrinsic viscosity of 0.7-0.8dL / g and a carboxyl content of 10-30mmol / kg.

[0025] Preferably, the heat stabilizer is at least one selected from inorganic phosphates such as phosphates, phosphites, hypophosphites, and pyrophosphates.

[0026] Preferably, the toughening agent is selected from at least one of glycidyl methacrylate (GMA) grafted hydrogenated styrene-butadiene copolymer (SEBS), maleic anhydride (MAH) grafted SEBS, and ethylene-butyl acrylate copolymer (EBA) grafted GMA.

[0027] The preferred amino silane coupling agent of the present invention is selected from at least one of 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysiloxane, anilinemethyltriethoxysiloxane, N,N-dimethyl-3-aminotrimethoxysiloxane, N(2-aminoethyl)3-propylaminomethoxymethylsilane, N-β-(aminoethyl)γ-aminopropyltriethoxysilane coupling agent, N-(β-aminoethyl-γ-aminopropyl)methyldimethoxysilane, silane-PEG-amino compound, 3-aminopropyltrihydroxysilane, diethylaminomethyltriethoxysilane, γ-piperazinylpropylmethyldimethoxysilane and γ-aminopropyltrimethoxysilane.

[0028] The titanium dioxide of the present invention is preferably at least one of rutile titanium dioxide and anatase titanium dioxide, and the preferred particle size is 200-400nm; further, the preferred particle size is 300nm; thereby, it is beneficial to improve the dispersibility of titanium dioxide in the polyester matrix, reduce agglomeration, and thus improve the optical properties and weather resistance of the film.

[0029] The mass ratio of titanium dioxide, deionized water and anhydrous ethanol in the preferred step (1) of the present invention is 100:(50-80):(20-50); thereby ensuring that the titanium dioxide powder is fully wetted and dispersed in the subsequent silane coupling agent modification process.

[0030] The mass of the aminosilane coupling agent in the preferred step (1) of the present invention is 5-10% of the mass of titanium dioxide; this ensures the optimal dispersion of titanium dioxide in the polyester matrix and also forms a chemical bond with the carboxyl group in the polyester matrix through the amino group of the coupling agent, thereby improving the overall performance of the film.

[0031] Preferably, the content of PBS phosphate buffer in step (1) is 20-30%.

[0032] The preferred mass ratio of terephthalic acid, ethylene glycol, tetrabutyl titanate, triethoxy phosphate, silicon-titanium core-shell material, and antioxidant in step (2) of the present invention is (80-100): (50-70): 1: 1: (200-260): 1; while ensuring a high conversion rate of the polyester polycondensation reaction, the weather resistance and mechanical properties of the film are further improved.

[0033] In the preferred embodiment of the present invention, the pre-stirring temperature in step (2) is 80-100°C and the pressure is 0.5-0.8 MPa; the pressure of the solid phase polycondensation is 220-260°C; and the temperature of the melt extrusion is 260-280°C.

[0034] Preferably, the antioxidant in step (2) is at least one selected from the group consisting of antioxidant 1010, antioxidant 1098, antioxidant 1024, antioxidant 168, and antioxidant 4426.

[0035] Another object of the present invention is to provide a method for preparing the fluorine-free weather-resistant polyester film as described above, characterized in that it comprises the following steps: S1: sending semi-matt polyethylene terephthalate high-viscosity chips, weather-resistant masterbatch, heat stabilizer and toughening agent to the extruder for melt extrusion; S2: After passing through the die, the melt is cast behind the chilled roller to form a thick sheet, and after longitudinal stretching, transverse stretching, shaping, cooling, pulling, and winding, a fluorine-free weather-resistant polyester film is obtained.

[0036] Specifically, in the above step S1, the extruder temperature is 260-280°C, the die temperature is 270-290°C; the chilled roller temperature is 10-30°C; the longitudinal stretching multiple is 2-4, and the transverse stretching multiple is 3-4; the setting temperature is 220-240°C, and the cooling temperature is 60-200°C; and the total thickness of the prepared fluorine-free weather-resistant polyester film is preferably 50±3μm.

[0037] The method for preparing a fluorine-free weather-resistant polyester film provided by the present invention has a simple processing flow, and the fluorine-free weather-resistant polyester film is prepared by a biaxial stretching processing technology, achieving the effects of uniform dispersion and strong interfacial force; compared with anti-aging additives on the market, the silicon-titanium core-shell material adopted by the present invention has a lower cost, and no solvent is required in the preparation process, and the reaction product does not need to be purified, and there is no solvent recovery, so the process is very environmentally friendly; in addition, the small molecular by-products generated during the solid-phase polycondensation reaction can flow out of the reaction system through vacuum or inert gas, so that the reaction is continuously carried out in the direction of the product, and the molecular weight of the product is continuously increased, thereby improving the molecular weight and mechanical properties; this method not only improves the weather resistance of the product, but also avoids the use of fluorides, meets environmental protection requirements, and has significant economic and environmental advantages. In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, specific embodiments of the present invention are described in detail below.

[0038] Unless otherwise specified, the semi-dull polyethylene terephthalate high-viscosity chips in the embodiments of the present invention and the comparative examples are purchased from Zhejiang Guxiandao Green Fiber Co., Ltd., with a viscosity of 0.78 dL / g; the heat stabilizer is phosphite, the toughening agent is maleic anhydride (MAH) grafted SEBS; the amino silane coupling agent is 3-aminopropyl triethoxysiloxane; the titanium dioxide is rutile titanium dioxide; the content of PBS phosphate buffer is 20%; the antioxidant is antioxidant 1010; the white masterbatch is purchased from Changzhou Futong Fiber Co., Ltd., and the filler is titanium dioxide, with a particle size of 300 nm and an ash content of 60%; the amounts of materials used in the embodiments and the comparative examples are all measured in parts by weight.

[0039] (1) According to the formula, titanium dioxide powder, deionized water and anhydrous ethanol were added to a 1000 mL three-necked flask equipped with a stirrer and a thermometer, stirred at room temperature for 30 min, and PBS phosphate buffer was gradually added using a dropping funnel until the pH value was 10; then the temperature was raised to 80 ° C and stirred for 2 h to fully infiltrate the titanium dioxide powder; 3-aminopropyl triethoxysiloxane was added and the stirring reaction was continued for 6 h; then the stirring was stopped, the mixture was cooled to room temperature, centrifuged and washed 4 times until the pH value of the surface liquid was 7, and the remaining solid mixture was dried to obtain a silicon-coated silicon-titanium core-shell material; (2) According to the formula, terephthalic acid, ethylene glycol, tetrabutyl titanate, triethoxy phosphate, silicon-titanium core-shell material, and antioxidant were added to the reactor, and inert gas nitrogen was introduced. The mixture was pre-stirred for 1 hour at a predetermined pressure of 0.5 MPa and 100°C, and the temperature was raised to 220°C and vacuumed for 4 hours for solid phase polycondensation. At the same time, ethylene glycol and small molecular water were continuously separated. After the reaction was completed, the temperature was lowered and granulated by a melt extruder to obtain a weather-resistant masterbatch with an ash content of 60%; The mass ratio of titanium dioxide powder, deionized water and anhydrous ethanol in step (1) is 100:50:50; the mass of aminosilane coupling agent in step (1) is 5% of the mass of titanium dioxide; the mass ratio of terephthalic acid, ethylene glycol, tetrabutyl titanate, triethoxy phosphate, silicon-titanium core-shell material and antioxidant in step (2) is 80:50:1:1:200:1; and the temperature of melt extrusion is 260°C.

[0040] (3) According to the formula, semi-matt polyethylene terephthalate high-viscosity chips, weather-resistant masterbatch, thermal stabilizer and toughening agent are sent to the extruder for melt extrusion. After passing through the die, the melt is cast on the chilled roller to form a thick sheet. After longitudinal stretching, transverse stretching, shaping, cooling, pulling and winding, a fluorine-free weather-resistant polyester film with a thickness of 50 μm is obtained.

[0041] Among them, the extruder temperature is 260°C, the die temperature is 270°C, the chill roller temperature is 10°C, the longitudinal stretching and transverse stretching multiples are 2.5 and 3, the setting temperature is 240°C, and the cooling section temperatures are 210, 170, 110, and 60°C.

[0042] (1) According to the formula, titanium dioxide powder, deionized water and anhydrous ethanol were added to a 1000 mL three-necked flask equipped with a stirrer and a thermometer, stirred at room temperature for 30 min, and PBS phosphate buffer was gradually added using a dropping funnel until the pH value was 10; then the temperature was raised to 90 ° C and stirred for 3 h to fully infiltrate the titanium dioxide powder; 3-aminopropyl triethoxysiloxane was added and the stirring reaction was continued for 7 h; then the stirring was stopped, the mixture was cooled to room temperature, centrifuged and washed 3 times until the pH value of the surface liquid was 7, and the remaining solid mixture was dried to obtain a silicon-coated silicon-titanium core-shell material; (2) According to the formula, terephthalic acid, ethylene glycol, tetrabutyl titanate, triethoxy phosphate, silicon-titanium core-shell material, and antioxidant were added to the reactor, and inert gas nitrogen was introduced. The mixture was pre-stirred for 1 hour at a predetermined pressure of 0.6 MPa and 90°C, and the temperature was raised to 240°C and vacuumed for 3 hours for solid phase polycondensation. At the same time, ethylene glycol and small molecular water were continuously separated. After the reaction was completed, the temperature was lowered and granulated by a melt extruder to obtain a weather-resistant masterbatch with an ash content of 60%; The mass ratio of titanium dioxide powder, deionized water and anhydrous ethanol in step (1) is 100:60:35; the mass of aminosilane coupling agent in step (1) is 7% of the mass of titanium dioxide; the mass ratio of terephthalic acid, ethylene glycol, tetrabutyl titanate, triethoxy phosphate, silicon-titanium core-shell material and antioxidant in step (2) is 90:60:1:1:230:1; and the temperature of melt extrusion is 270°C.

[0043] (3) According to the formula, semi-matt polyethylene terephthalate high-viscosity chips, weather-resistant masterbatch, thermal stabilizer and toughening agent are sent to the extruder for melt extrusion. After passing through the die, the melt is cast on the chilled roller to form a thick sheet. After longitudinal stretching, transverse stretching, shaping, cooling, pulling and winding, a fluorine-free weather-resistant polyester film with a thickness of 53 μm is obtained.

[0044] Among them, the extruder temperature is 270°C, the die temperature is 280°C, the chilled roller temperature is 30°C, the longitudinal and transverse stretching multiples are 4, 4, the setting temperature is 230°C, and the cooling section temperatures are 210, 170, 110, and 60°C.

[0045] (1) According to the formula, titanium dioxide powder, deionized water and anhydrous ethanol were added to a 1000 mL three-necked flask equipped with a stirrer and a thermometer, stirred at room temperature for 30 min, and PBS phosphate buffer was gradually added using a dropping funnel until the pH value was 10; then the temperature was raised to 80 ° C and stirred for 2 h to fully infiltrate the titanium dioxide powder; 3-aminopropyl triethoxysiloxane was added and the stirring reaction was continued for 6 h; then the stirring was stopped, the mixture was cooled to room temperature, centrifuged and washed 4 times until the pH value of the surface liquid was 7, and the remaining solid mixture was dried to obtain a silicon-coated silicon-titanium core-shell material; (2) According to the formula, terephthalic acid, ethylene glycol, tetrabutyl titanate, triethoxy phosphate, silicon-titanium core-shell material, and antioxidant were added to the reactor, and inert gas nitrogen was introduced. The mixture was pre-stirred for 1 hour at a predetermined pressure of 0.8 MPa and 80°C, and the temperature was raised to 265°C and vacuumed for 4 hours for solid phase polycondensation. At the same time, ethylene glycol and small molecular water were continuously separated. After the reaction was completed, the temperature was lowered and granulated by a melt extruder to obtain a weather-resistant masterbatch with an ash content of 60%; The mass ratio of titanium dioxide powder, deionized water and anhydrous ethanol in step (1) is 100:80:20; the mass of aminosilane coupling agent in step (1) is 10% of the mass of titanium dioxide; the mass ratio of terephthalic acid, ethylene glycol, tetrabutyl titanate, triethoxy phosphate, silicon-titanium core-shell material and antioxidant in step (2) is 100:70:1:1:255:1; and the temperature of melt extrusion is 260°C.

[0046] (3) According to the formula in Table 1, each component was sent to an extruder for melt extrusion. After passing through the die, the melt was cast on a chilled roller to form a thick sheet. After longitudinal stretching, transverse stretching, shaping, cooling, pulling, and winding, a fluorine-free weather-resistant polyester film with a thickness of 50 μm was obtained.

[0047] Among them, the extruder temperature is 280°C, the die temperature is 290°C, the chilled roller temperature is 19°C, the longitudinal stretching and transverse stretching multiples are 3.3 and 3.3, the setting temperature is 220°C, and the cooling section temperatures are 210, 170, 110, and 60°C.

[0048] The preparation method of the fluorine-free weather-resistant polyester film in Examples 4-7 is the same as that in Example 3.

[0049] The non-amino weather-resistant masterbatch in the comparative example of the present invention is prepared according to the following method: (1) According to the formula, titanium dioxide powder, deionized water and anhydrous ethanol were added to a 1000 mL three-necked flask equipped with a stirrer and a thermometer, stirred at room temperature for 30 min, and PBS phosphate buffer was gradually added using a dropping funnel until the pH value was 10; then the temperature was raised to 80 ° C and stirred for 2 h to fully infiltrate the titanium dioxide powder; γ-mercaptopropyltrimethoxysilane was added and the stirring reaction was continued for 6 h; then the stirring was stopped, the mixture was cooled to room temperature, centrifuged and washed 4 times until the pH value of the surface liquid was 7, and the remaining solid mixture was dried to obtain a silicon-coated non-amino silicon-titanium core-shell material; (2) According to the formula, terephthalic acid, ethylene glycol, tetrabutyl titanate, triethoxy phosphate, non-amino silicon-titanium core-shell material, and antioxidant are added to the reactor, and inert gas nitrogen is introduced. The mixture is pre-stirred for 1 hour at a predetermined pressure of 0.8 MPa and 80°C, and the temperature is raised to 265°C and vacuumed for 4 hours for solid phase polycondensation. At the same time, ethylene glycol and small molecular water are continuously separated. After the reaction is completed, the temperature is lowered and granulated by a melt extruder to obtain a non-amino weather-resistant masterbatch with an ash content of 60%; The mass ratio of titanium dioxide powder, deionized water and anhydrous ethanol in step (1) is 100:80:20; the mass of the amino silane coupling agent in step (1) is 10% of the mass of titanium dioxide; the mass ratio of terephthalic acid, ethylene glycol, tetrabutyl titanate, triethoxy phosphate, non-amino silicon-titanium core-shell material and antioxidant in step (2) is 100:70:1:1:255:1; and the temperature of melt extrusion is 260°C.

[0050] Various parameters in the preparation process of the fluorine-free weather-resistant polyester films of various embodiments of the present invention and comparative examples are shown in Table 1.

[0051] Table 1 .

[0052] The various measured values ​​shown in the various embodiments of the present invention and the comparative examples are measured according to the following methods.

[0053] Hydrolysis resistance test: (1) Strength / elongation at break: tested according to the method in GB / T 13542.2-2009.

[0054] (2) PCT test: 121°C, 100% RH, 2 atm, 72 h; instrument: high pressure cooking pot.

[0055] UV aging resistance test: (1) UV blocking rate: wavelength range: 280-380nm, instrument: UV spectrophotometer; (2) UV aging: UV aging treatment is carried out according to the method in IEC 61215. Light source: halogen lamp, with a cumulative energy of 60 kwh / m 2 Start the test, instrument: UV aging box; (3) Yellowing index △b: Use a UV spectrophotometer to test the film after UV aging treatment.

[0056] The properties of the fluorine-free weather-resistant polyester films in the embodiments of the present invention and the comparative examples are shown in Table 2.

[0057] Table 2 .

[0058] It can be seen from the performance test data of each embodiment and comparative example in Table 2 that, compared with the use of conventional titanium dioxide and non-amino weather-resistant masterbatch, adding the weather-resistant masterbatch prepared in the present invention during the preparation process of fluorine-free weather-resistant polyester film can significantly improve the hydrolysis resistance and UV aging resistance of the film.

[0059] The difference between Comparative Example 1 and Example 3 is that the weathering masterbatch prepared by the present invention is not added to Comparative Example 1, while the weathering masterbatch prepared by the present invention is added to Example 3. The aminosilane coupling agent in the weathering masterbatch can effectively react with the carboxyl or ester group generated during the PCT treatment process, thereby improving the elongation at break retention rate of the sample after the PCT 72H test. In addition, due to the shielding effect and nanoscale characteristics of titanium dioxide, the UV blocking rate of Example 3 is significantly improved, and at 60kwh / m 2 Under ultraviolet irradiation, the yellowing index is significantly reduced, which improves its resistance to ultraviolet aging.

[0060] The difference between Comparative Examples 2, 3, 4 and Examples 3, 4, 5 is that Examples 3, 4, 5 add the weathering masterbatch prepared by the present invention, while Comparative Examples 2, 3, 4 only add conventional titanium dioxide as the weathering masterbatch. The retention rate of the elongation at break of Examples 3, 4, 5 after PCT 72H is significantly improved, which is due to the end-capping effect of the aminosilane coupling agent coated on the outer layer of the weathering masterbatch, which reduces the carboxyl content in the system and slows down the further hydrolysis of the film. Although increasing the content of titanium dioxide may increase the brittleness of the film and reduce its mechanical properties, the retention rate of the elongation at break of Examples 3, 4, 5 is still significantly advantageous. In addition, the 60 kwh / m 2 The yellowing index of Examples 4, 5 and 6 is lower than that of Comparative Example 1, but the decrease is more obvious. This is due to the fact that the titanium dioxide coated with the aminosilane coupling agent can react with the carboxyl group in the polyester, so that the titanium dioxide and the polyester have a good interface interaction, which improves its dispersibility and improves its resistance to ultraviolet aging.

[0061] The difference between Comparative Examples 5, 6, and 7 and Examples 3, 4, and 5 is that Examples 4, 5, and 6 add the weathering masterbatch prepared by the present invention, while Comparative Examples 5, 6, and 7 add titanium dioxide coated with non-amino silane coupling agent as the weathering masterbatch. The PCT breaking elongation retention rate of Comparative Examples 5, 6, and 7 after 72H decreases significantly, which is not much different from Comparative Example 1, indicating that the non-amino silane coupling agent does not have the effect of alleviating the hydrolysis of the polyester film; in addition, the 60 kwh / m 2 The yellowing index under is also significantly higher than that of Examples 3, 4, and 5, indicating that the non-aminated silane coupling agent has little effect on improving the dispersibility of titanium dioxide in the polyester film and is not very helpful in improving its UV resistance.

[0062] The difference between Comparative Example 8 and Example 3 is that Comparative Example 8 reduces the amount of weather-resistant masterbatch added, and the retention rate of elongation at break of the prepared polyester film PCT72H is reduced, the UV blocking rate is reduced, and the yellow edge index is increased, indicating that a small amount of added weather-resistant masterbatch has little effect on improving the hydrolysis resistance and UV aging resistance of the polyester film.

[0063] The difference between Comparative Example 9 and Example 3 is that Comparative Example 9 reduces the amount of weather-resistant masterbatch added, and the retention rate of elongation at break of the prepared polyester film PCT72H is significantly reduced, the UV blocking rate is increased, and the yellow edge index is reduced, indicating that excessive weather-resistant masterbatch can improve the UV aging resistance of the polyester film, but excessive fillers will directly reduce the mechanical properties of the polyester film PCT before and after aging.

[0064] It can be seen from the above data that the present invention introduces titanium dioxide modified by a silane coupling agent into PET polyester to form a silicon-titanium core-shell material, and then prepares a weather-resistant masterbatch by solid-phase polycondensation with the polyester raw material. By utilizing the synergistic effect between the components, the production cost is reduced while the prepared fluorine-free weather-resistant polyester film has excellent hydrolysis resistance and UV resistance, and its weather resistance is significantly improved.

[0065] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.

Claims

1. A fluorine-free weather-resistant polyester film, characterized in that: According to parts by weight, it includes the following components: 70-90 pieces of semi-matt polyethylene terephthalate high-viscosity slices; Weathering masterbatch 8-28 parts; The weather-resistant masterbatch is obtained by modifying titanium dioxide with a silane coupling agent to form a silicon-titanium core-shell material, and then solid-phase polycondensing the material with a polyester raw material.

2. The fluorine-free weather-resistant polyester film according to claim 1, characterized in that: The components of the fluorine-free weather-resistant polyester film also include a heat stabilizer and a toughening agent; and the semi-matt polyethylene terephthalate high-viscosity slice has an intrinsic viscosity of 0.7-0.8 dL / g and a carboxyl content of 10-30 mmol / kg.

3. The fluorine-free weather-resistant polyester film according to claim 1, characterized in that: The weather-resistant masterbatch is prepared according to the following method: (1) Add titanium dioxide, deionized water, and anhydrous ethanol to a container and stir, then gradually add PBS phosphate buffer until the pH is 10; heat up and continue stirring; then add amino silane coupling agent and continue stirring and reacting for 6-7 hours; after cooling to room temperature, centrifuge and wash until the surface liquid pH is 7, and dry the remaining solid mixture to obtain a silicon-coated silicon-titanium core-shell material; (2) Add terephthalic acid, ethylene glycol, tetrabutyl titanate, triethoxy phosphate, silicon-titanium core-shell material, and antioxidant into a container, pre-stir under the protection of inert gas, then increase the temperature and carry out solid phase polycondensation reaction under vacuum, and after cooling, granulate through a melt extruder to obtain a weather-resistant masterbatch.

4. The fluorine-free weather-resistant polyester film according to claim 3, characterized in that: The amino silane coupling agent is selected from at least one of 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysiloxane, anilinemethyltriethoxysiloxane, N,N-dimethyl-3-aminotrimethoxysiloxane, N(2-aminoethyl)3-propylaminomethoxymethylsilane, N-β-(aminoethyl)γ-aminopropyltriethoxysilane coupling agent, N-(β-aminoethyl-γ-aminopropyl)methyldimethoxysilane, silane-PEG-amino compound, 3-aminopropyltrihydroxysilane, diethylaminomethyltriethoxysilane, γ-piperazinepropylmethyldimethoxysilane, and γ-aminopropyltrimethoxysilane.

5. The fluorine-free weather-resistant polyester film according to claim 3, characterized in that: The titanium dioxide is at least one of rutile titanium dioxide and anatase titanium dioxide.

6. The fluorine-free weather-resistant polyester film according to claim 3, characterized in that: The mass ratio of titanium dioxide, deionized water and anhydrous ethanol in step (1) is 100:(50-80):(20-50).

7. The fluorine-free weather-resistant polyester film according to claim 3, characterized in that: The mass of the amino silane coupling agent in step (1) is 5-10% of the mass of titanium dioxide.

8. The fluorine-free weather-resistant polyester film according to claim 3, characterized in that: The mass ratio of terephthalic acid, ethylene glycol, tetrabutyl titanate, triethoxy phosphate, silicon-titanium core-shell material, and antioxidant in step (2) is (80-100):(50-70):1:1:(200-260):

1.

9. The fluorine-free weather-resistant polyester film according to claim 3, characterized in that: The pre-stirring temperature in step (2) is 80-100°C and the pressure is 0.5-0.8 MPa; the pressure of the solid phase polycondensation is 220-260°C; and the temperature of the melt extrusion is 260-280°C.

10. A method for preparing a fluorine-free weather-resistant polyester film according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1: sending semi-matt polyethylene terephthalate high-viscosity chips, weather-resistant masterbatch, heat stabilizer and toughening agent to the extruder for melt extrusion; S2: After passing through the die, the melt is cast behind the chilled roller to form a thick sheet, and after longitudinal stretching, transverse stretching, shaping, cooling, pulling, and winding, a fluorine-free weather-resistant polyester film is obtained.

Citation Information

Cited By

  • Super-weather-resistant fluorocarbon powder coating

    CN120158163A